Classification of tracheal stenosis with asymmetric misclassification errors from EMG signals using an adaptive cost-sensitive learning method - Volk, Ohad; Ratnovsky, Anat; Naftali, Sara; Singer, Gonen (Biomedical signal processing and control, 2023)
Upper airway obstruction is characterized by loss of normal airway architecture resulting from various disorders such as infections and asthma. Early detection of airway obstruction is essential to prevent medical deterioration. The objective of this study was to non-invasively identify early-stage tracheal stenosis, using electromyography (EMG) signals of inspiratory muscles. The identification of tracheal stenosis has been defined as an asymmetric misclassification cost problem. Specifically, the EMG signals are used as input to a ResNet-like architecture for tabular data with an Adaptive Cost-Sensitive Learning (AdaCSL) algorithm. The electrical activity of the external intercostal muscle of four healthy individuals was recorded while they breathed through two different tubes, one simulating a narrowed airway and the other simulating a normal airway. Two experiment settings were designed. The first setting aimed to classify tracheal stenosis in a specific subject by training the model on data from other subjects, reflecting the case of diagnosing a new subject. To overcome multi-subject variations, the second setting aimed to classify tracheal stenosis by mixing all subjects’ training and test data. The ResNet-like architecture with an AdaCSL algorithm was significantly better in the first experiment setting with costs that were 43%, 48%, and 59% lower than the cost of the second-best alternative for three different misclassification cost values. It also achieved a lower cost in the second experiment setting over other classifiers. The experiments emphasize the capability of using inspiratory muscle EMG signals to diagnose respiratory disease and demonstrate the usefulness of the AdaCSL algorithm for personalized monitoring. [Display omitted] •EMG signals were used for the early identification of tracheal stenosis existence.•The adaptive cost-sensitive learning (AdaCSL) algorithm was applied.•Two machine learning experiments settings were designed.•Identification was made based on data of other subjects and mixed data.•EMG signals and AdaCSL are useful for tracheal stenosis identification.